Stock Identification of Brown-Striped Snapper, Lutjanus vitta (Qouy and Gaimard, 1824), Inferred From Otolith Shape Analysis off the Coast of Iligan Bay, Mindanao, Philippines - MARICEL TUMAMPOS GUMOLOC; IVANE R. PEDROSA-GERASMIO (Asian Fisheries Science)
Otolith shape analysis is an effective method that has been used to separate stocks based on their phenotypic traits. The brown-striped snapper, Lutjanus vitta (Quoy and Gaimard, 1824), is an important component of the fish catch in Iligan Bay, Mindanao, Philippines. Trends in catch and catch per unit effort, however, had been declining because of overfishing of this economically significant species as a result of continuous human exploitation. To accurately identify and manage fish, one must be aware of the stock structure of a species. The aim of this study was to contribute to the knowledge on the stock identification of L. vitta using otolith morphometrics and shape analysis. A total of 90 individuals of L. vitta were collected from the three selected sampling locations in Iligan Bay: Iligan City, Kapatagan, and Oroquieta City. Results of ANOVA tests investigating otolith shape differences between areas showed that mean values among sites differed significantly for the following shape indices: ellipticity (F = 20.93, P < 0.001), aspect ratio (F = 19.45, P < 0.001), and circularity (F = 24.72, P < 0.001). A canonical analysis of principal components verified the separation of otolith morphometric parameters among locations, with 73.9 % of the variation explained by the first axis (PC1). However, otolith shape did not differ significantly between sexes (P > 0.05). Furthermore, the differences in otolith shape among the three locations suggests a spatial structuring of L. vitta in Iligan Bay (P = 0.001) and necessitates local management and policies to enable sustainable management of the fisheries.